Evaluation methodology for national enterprise architecture frameworks - Kostoska, Magdalena; Gushev, Marjan; Kiroski, Kiril (My University, 2010)
This article introduces a new methodology for NEA (National Enterprise Architecture) evaluation based on two sets of indicators. The first set consists of quantitative indicators regarding to the e-government initiatives and their characteristics, including interoperability strategy, NEA strategy, legal framework and legislatives, sustainability, quality control, dissemination and predicted goals. The second set is based on the definition of NEA and NEA characteristics, consisting of the following quantitative indicators: methodology and models, model interfaces, architectural standards and principles, repository and use of development indicator. The final result of the evaluation is calculated as a sum of the results of the both sets of indicators. In this paper we analyze how similar efforts resulted in smaller methodology and evaluate several NEA initiatives with comparison of results. Further we comment how our approach results in a new sophistication methodology that can be used to evaluate NEA initiatives and help others in giving directions to build new sophisticated solutions.
Keywords: National enterprise architecture evaluation framework, quantitative evaluation framework, e-Government, e-Services benchmarking